Cholangiocarcinoma Among Children and Adolescents: A Review of the Literature and Surveillance, Epidemiology, and End Results Program Database Analysis. Issue 1 (January 2018) - Newsome, Jennifer R.; Venkatramani, Rajkumar; Heczey, Andras; Danysh, Heather E.; Fishman, Douglas S.; Miloh, Tamir
ABSTRACT: Objective: Cholangiocarcinoma (CCA) is a biliary malignancy found primarily in adults. The incidence of CCA in children is unknown. The aim of this study was to describe characteristics of CCA in children and adolescents. Methods: Using the Surveillance, Epidemiology, and End Results Program (SEER 18) database, we identified incident cases of CCA diagnosed at <20 years of age during the period of 1973 to 2013. Additionally, we reviewed published case reports describing pediatric patients with CCA. We calculated descriptive statistics for CCA cases identified in SEER and in case reports. Kaplan–Meier analysis was performed to determine median and 3-year overall survival (OS) rates. Results: We identified 15 children and adolescents diagnosed as having CCA from SEER 18 with an incidence rate of 0.0036 per 100, 000. Two-thirds of cases were male, and the majority were white (n = 10). The median age at diagnosis was 17 years (range: 11–19 years). Nine tumors were intrahepatic, 3 extrahepatic, and 3 unspecified. One-third had distal metastases at diagnosis. Eight patients underwent surgical resection including liver transplant in two. Six patients were alive at the time of follow-up. Patients without surgical treatment did not survive. Three-year OS was 50%. Twenty-two children with CCA were found in the literature with a median age at diagnosis of 15 years (range: 3–18 years). Half were male, and 90% had an underlying gastrointestinal comorbidity. Three-year OS was 35.3%. Conclusions: CCA in children and adolescents is rare with poor survival. A high proportion of cases had a history of biliary disease. Surgical resection is necessary for cure.